Implementation of Administrative Law Court Decisions by Administrative Agencies or Officials - Sabili Casba Ar-Rusd; Sitta Khairunnisa; Bimo Satrio Wicaksono; Dimas Gibran Satrio Utomo; Taufiq Alamsyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The implementation of decisions issued by the State Administrative Court (PTUN) constitutes a critical element in ensuring the effectiveness of judicial review over governmental action and maintaining administrative accountability within a rule-of-law framework. This study examines the implementation of PTUN decisions by administrative bodies or state administrative officials through a non-empirical legal research design employing a normative juridical approach. The analysis is conducted using statutory, conceptual, and doctrinal approaches based on legislation, legal doctrines, judicial norms, and scholarly literature concerning administrative justice and execution mechanisms. The findings demonstrate that although PTUN decisions possess final and binding legal force, their implementation remains constrained by fragmented execution arrangements, limited coercive instruments, absence of detailed implementing regulations concerning administrative sanctions and forced payments, and continued dependence on voluntary compliance by administrative officials. These conditions weaken legal certainty, reduce the effectiveness of judicial protection, and hinder the realization of the General Principles of Good Governance (AUPB). The study argues that implementation should be reconstructed as an integrated legal process supported by stronger enforcement mechanisms, institutional coordination, and a compliance-oriented administrative culture to enhance the authority of administrative adjudication and strengthen accountable governance.